The reproductive biology of the solitary Cape mole-rat, Georychus capensis and the social Natal mole-rat, Cryptomys hottentotus natalensis (Rodentia : Bathyergidae) - Bennett, Nigel Charles (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.